Relationship Between Gender and 1-Year Mortality in ANCA-Associated Vasculitis Patients: A Single-Center Retrospective Analysis and Meta-Analysis - Zhu, Qing; Li, Fen; Xie, Xi; Chen, Bilin; Yu, Qianwen; Wei, Yusong; Ge, Yan (Frontiers in Medicine, 2022)
Objective The relationship between gender and short-term prognosis of patients with anti-neutrophil cytoplasmic antibody (ANCA) associated vasculitis (AAV) is unclear, hence single-center retrospective analysis and meta-analysis were conducted to determine the relationship. Methods Initially treated patients with AAV were retrospectively enrolled. Data of clinical manifestation, laboratory indicators, Birmingham vasculitis activity score (BVAS), therapeutic treatments, and the patients' situations within 1 year were recorded. First, we compared the basic characteristics between male and female patients. Second, the risk factors associated with a 1-year mortality rate of patients with AAV were evaluated. Finally, a meta-analysis was performed to explore the effect of gender on 1-year mortality in patients with AAV. Results The study involved 84 patients with AAV, including 33 female and 51 male participants. In total, 14 people died (12 males and 2 females) and 70 survived in the 1st year. Statistical differences were noted in the age of onset, the course of the disease, WBC, HB, N, ESR, CRP, BUN, ALT and ALB, BVAS, and 1-year mortality rate between male and female participants. In male patients, elevated Scr, NLR, PLT, and RDW-CV were associated with poor AAV (P < 0.05) prognosis. The meta-analysis verified that male gender was an independent risk factor for the 1-year mortality of patients with AAV(OR = 1.54). Conclusion Significant sex-specific differences were found in patients with AAV. Male patients contributed to 1.54-fold of 1-year mortality risk in patients with AAV by meta-analysis. More attention should be paid to the mortality risk of male patients with AAV in the early stage.